Ефект Матвія в українському бібліотекознавстві - Назаровець, Сергій Андрійович (Видавництво Львівської політехніки, 2012)
Досліджено вплив ефекту Матвія на розподіл цитувань публікацій вітчизняних бібліотекознавців та запропоновано шляхи подолання негативної дії цього ефекту. The article “Matthew Effect in Ukrainian Library Science” by S. Nazarovets describes the influence of Matthew effect on the distribution of citations of Ukrainian scientist librarians’ publications and suggested ways of overcoming the negative impact of this effect.
Keywords: ефект Матвія; бібліотекознавчі онлайн-публікації; цитат-аналіз; наукова комунікація; Google Академія; Matthew effect; online publications of scientist librarians; citation analysis; scholarly communication; Google Scholar